Spatiotemporal changes and driving factors of droughts in Huaihe river basin using meteorological and vegetation indices - Chong Xu; Xiaomeng Song; Yanli Liu; Yifan Zou; Nantao Xu; Ying Zhang; Hao Chen (Journal of Hydrology: Regional Studies, 2025)
Study area: Huaihe River Basin (HRB), China Study focus: This study analyzed the effects of drought on vegetation in the HRB using measured meteorological data (SPEI) and remotely sensed vegetation data (VHI) to quantify the trends, spatial distribution, and multi-year return periods of meteorological drought and vegetation health in the HRB. Concurrently, the study identified the predominant drivers of meteorological drought and vegetation health. The analysis revealed that the spatial and temporal variations of SPEI and VHI are pivotal in identifying areas susceptible to drought and quantifying its extent. New hydrological insights for the region: Drought threatens water resources, agriculture and ecosystems in the HRB. In this study, we combined the SPEI and VHI to assess drought dynamics and drivers from 1982 to 2020 using Copula model and random forest analysis. Driven by warming-induced droughts, winter-spring droughts intensified and VHI decreased in the northern sub-basin, while vegetation health remained stable in the southern region. A 3-month lag between SPEI and VHI indicated a delayed vegetation response to meteorological droughts. The covariance model revealed a non-linear relationship between drought duration and intensity. The correlation between vegetation drought and meteorological drought in HRB showed significant sub-basin differences, with YR and LG having the highest combined drought risk, while WB and BH showed greater drought resilience due to natural or anthropogenic regulation. Random forest analyses showed that precipitation was the main driver of both indices, with soil moisture influencing SPEI through hydrology and temperature influencing VHI through vegetation physiology.